Biology and population genetics of Pyricularia oryzae for rice blast control in Mali - (:unkn) unknown (My University, 2021)
Rice production is affected by several plant pathogens, including the fungus Pyricularia oryzae, which causes blast disease. This disease is a major constraint to the intensification of rice production in the world. To improve integrated pest management, it is necessary to know the sources of inoculum and useful information on the diversity of the pathogen. However, presently, the disease prevalence and the relative importance of inoculum sources have not been assessed in West Africa and, more specifically, in Mali. Similarly, the genetic diversity and population structure of P. oryzae are poorly documented in Africa.The general objective of this thesis is, therefore, to contribute to filling this knowledge gap, and the specific objectives are 1) to assess the incidence and severity of rice blast in different rice-growing areas in Mali, 2) to determine whether seeds, straw, and/or wild rice are sources of inoculum for cultivated rice, and 3) to determine the population structure of P. oryzae in Africa.Surveys conducted in farmers' and experimental plots in 2018 allowed to observe leaf and panicle blast in 10 out of 17 sites surveyed. In symptomatic fields, leaf incidence ranged from 24 to 72% and leaf severity from 2 to 15%. The highest values of panicle incidence and severity reached 94% and 52%, respectively. In 2019, leaf blast was observed on 3 out of 4 sites surveyed, and incidence and severity were much lower (maximum of 7% and 1%, respectively). Incidence and severity were not significantly different between irrigated and rainfed-lowland agrosystems. The highest values for panicle blast incidence and severity confirm that blast is a potential cause of high yield losses.The analysis of seed mycoflora showed the presence of the genera Bipolaris and Curvularia in 17 of the 20 plots with averages of 4.6 and 4.3% of contaminated seeds, respectively. The third pathogen observed was a fungus of the genus Fusarium. P. oryzae was not detected on the seed
Keywords: African Research